Visible price increases could trigger political backlash and policy reversal. - Barthes (Isonomia, 2025)
Visible price increases could trigger political backlash and policy reversal.
iso-id: iso:argument:6eGgjyJF; sha256: sha256:f4eb1a835c7b6d27aab61ec45156587fc8ed9325d1599c22b4b490ea5581404d